Approximate solutions of finite dynamic spherical cavity-expansion models for penetration into elastically confined concrete targets. (April 2018) - Meng, Chaomei; Tan, Qinghua; Jiang, Zhigang; Song, Dianyi; Liu, Fei
Highlights: The modified Griffith criterion was firstly used to describe the strength feature of concrete in comminuted region for confined concrete targets and the reference range of dimensionless parameter m is recommended. A finite dynamic spherical cavity expansion model was proposed for radially confined concrete targets. A model to predict the depth of penetration (DOP) for confined concrete target under impact of rigid projectile was developed, and comparisons between the calculated and tested DOP of APP penetrating into steel-tube-confined concrete (STCC) targets were carried out. Abstract: Confined concrete has superior anti-penetration performance over unconfined concrete. A finite dynamic spherical cavity-expansion approximation model with radially elastic confinement is proposed to analyze the confinement on concrete targets and predict the depth of penetration (DOP), taking steel-tube-confined concrete (STCC) targets normally penetrated by rigid projectiles as an example. Firstly, the validity of a nonlinear failure criterion to describe strength feature of concrete in the comminuted region is demonstrated by triaxial compressible tested data and the reference range of dimensionless parameter m in the modified Griffith criterion is recommended. Secondly, the relationship between the stresses in concrete and cavity-expansion velocity is developed. Furthermore, the confinement effects on response modes of confined concrete, radial stress at cavity wall and stresses distribution in concrete are analyzed. Lastly, an engineering model is also established to predict the DOP of STCC targets normally penetrated by rigid projectiles. The results show that the radial stress at cavity wall is not a constant during the cavity-expansion process in finite concrete with radially elastic confinement, which is different from the steady spherical cavity-expansion of infinite material in which the radial stress at cavity wall is a constant with constant cavity-expansion velocity. The possible response phases of confined concrete targets normally penetrated by rigid projectiles include "elastic-cracked-comminuted", "cracked-comminuted" and "full-comminuted", depending on the relationship among cavity-expansion velocity, radial confining stiffness and radius ratio of cavity to target. The DOP data from the engineering model established in this paper agree well with those of experiments in the published references.